Implementing the collective impact model as a gateway to a veterans community navigator program. (2nd January 2023) - Wagner, Beverly; Felderhoff, Brandi; Solomon, Kay
ABSTRACT: Addressing mental health needs and homelessness among the veteran population calls for a coordinated systemic response that is all too often missing from community-based responses. The collective impact (CI) model provides a framework for community collaboration to address entrenched problems by increasing collaboration across sectors. This study used a qualitative descriptive approach to explore the use of CI to develop a veterans' community navigator program within a community in the Southwestern United States (US). Data was gathered and thematically analyzed from interviews with key stakeholders (N = 7). Findings from this study support the use of the CI model for program development and implementation and suggest that the CI model may be enhanced with strategic approaches that 1) consider the target population as stakeholders, 2) strategize communication to build sustainable partnerships, and 3) use thorough community needs assessments to inform program development.